Productivity dispersion and intermediate inputs in European industries - Juvonen, Juha (My University, 2025)
Aim of this study is to study the effect of intermediate inputs to productivity dispersion with European sector level data. Secondary objectives are to evaluate the models used and review characteristics of the intermediate inputs, productivity dispersion and related literature. It is found that while the models have trouble giving robust estimates with the data, the results are still in line with the literature and that they highlight the fact that choice between gross output and value added total factor productivity methods is not trivial.
Keywords: Productivity, Intermediate inputs